let X be RealNormSpace; :: thesis: for f, g, h being Point of () holds
( h = f - g iff for x being VECTOR of X holds h . x = (f . x) - (g . x) )

let f, g, h be Point of (); :: thesis: ( h = f - g iff for x being VECTOR of X holds h . x = (f . x) - (g . x) )
reconsider f9 = f, g9 = g, h9 = h as Lipschitzian linear-Functional of X by Def9;
hereby :: thesis: ( ( for x being VECTOR of X holds h . x = (f . x) - (g . x) ) implies h = f - g )
assume h = f - g ; :: thesis: for x being VECTOR of X holds h . x = (f . x) - (g . x)
then h + g = f - (g - g) by RLVECT_1:29;
then A11: h + g = f - (0. ()) by RLVECT_1:15;
now :: thesis: for x being VECTOR of X holds (f9 . x) - (g9 . x) = h9 . x
let x be VECTOR of X; :: thesis: (f9 . x) - (g9 . x) = h9 . x
f9 . x = (h9 . x) + (g9 . x) by ;
hence (f9 . x) - (g9 . x) = h9 . x ; :: thesis: verum
end;
hence for x being VECTOR of X holds h . x = (f . x) - (g . x) ; :: thesis: verum
end;
assume A2: for x being VECTOR of X holds h . x = (f . x) - (g . x) ; :: thesis: h = f - g
now :: thesis: for x being VECTOR of X holds (h9 . x) + (g9 . x) = f9 . x
let x be VECTOR of X; :: thesis: (h9 . x) + (g9 . x) = f9 . x
h9 . x = (f9 . x) - (g9 . x) by A2;
hence (h9 . x) + (g9 . x) = f9 . x ; :: thesis: verum
end;
then f = h + g by Th35;
then f - g = h + (g - g) by RLVECT_1:def 3;
then f - g = h + (0. ()) by RLVECT_1:15;
hence h = f - g ; :: thesis: verum